Language Practices Among Children and Youth in Indonesia - Kushartanti, Bernadette; Djenar, Dwi Noverini; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book presents studies of language use in Indonesia, focusing on children and youth. It reports on developments in the use of language for narrative production and within the realm of popular culture and traditional cultural practices in Indonesia. Through studies that include cohesion in narrative production, language in radio advertising, naming practices and formulaic prohibitions in Javanese, and speech presentation in popular fiction, the book provides insights into how sociocultural changes are reflected in language. This book is a useful resource for students and scholars conducting research on language and cultural practices in Indonesia, particularly in relation to children and young people.
1. Grammatical Cohesion in Indonesian Pre-schoolers' Narrative -- 2. Gender and Cohesion in Indonesian Pre-schoolers' Narrative -- 3. Indonesian Lexical Cohesion in Javanese School-age Children's Narrative -- 4. Superstructure and Cohesion in Jarkartan Sign Langauge -- 5. Humor and Violation of Cooperative Principles in Cartoon -- 6. Playing with Language: Indonesian Youth in Interaction -- 7. Adlibs in Indonesian Radio Advertising -- 8. The Discourse of Motivation: Judges' Comments in Voice Kids Indonesia -- 9. Graphemic Transcription of Javanese in Instant Messaging Apps -- 10. Javanese Personal Names in Traditional and Global Contexts: A Semiotic Study -- 11 Children and the Interpretation of Gugon Tuhon: The Age Factor.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Sociolinguistics; Asia -- Languages; Applied linguistics; Youth -- Social life and customs; Sociolinguistics; Asian Languages; Applied Linguistics; Youth Culture